Dry Matter Accumulation, Seasonal Uptake and Partitioning of Mineral Nutrients by Vitis vinifera L. cv. Sultanina Grapevines in the Lower Orange River Region of South Africa - A Preliminary Investigation - Conradie, W.J.; Raath, P.J.; Mulidzi, A.R.; Howell, C.L. (South African Journal of Enology and Viticulture, 2022)
Table grapes are harvested from November until early February in the Orange River Region of South Africa, where a functional leaf canopy is present for up to six months of post-harvest. Seasonal uptake and partitioning of mineral nutrients by ‘Sultanina’ grapevines in this long-season area were quantified in a preliminary investigation. Entire grapevines growing on two different soil types were sampled during the growing season. On sandy soil, further from the river, grapevine vigour was not excessive; however, on the fertile alluvial soil vigour was higher with active post-harvest re-growth. At budbreak, reserve N played an important role on the sandy soil, while it was less important on the alluvial one. During the postharvest period, 34.3% of the annual N-requirement was absorbed by grapevines cultivated on sandy soil at post-harvest, while only 17.0% was absorbed on the alluvial soil. Approximately 4.0 kg N was utilized for the production of one ton of fresh grapes. A major fraction of the annual P-requirement (41.9%) was absorbed post-harvest by grapevines on the sandy soil. Grapevines on alluvial soil absorbed more P at pre-harvest; however, P was somehow lost post-harvest. Comparable amounts of K and Mg were absorbed by both selections of grapevines. Sandy soil grapevines absorbed K and Mg at post-harvest, while a net loss occurred for those of alluvial soil. Calcium utilized by sandy soil grapevines was less than half that utilized by those of alluvial soil. The seasonal absorption pattern of Ca was comparable for both soils. Results suggest that that seasonal uptake and partitioning of mineral nutrients are affected by soil type and grapevine vigour.